Maturity Assessment at a University IT Center Using COBIT 2019 EDM and APO Domains - Zufria, Ilka; Muhammad Siddik Hasibuan (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – This study evaluates the capability of IT governance at Pustipada UIN Sumatera Utara Medan to determine whether current technology practices are aligned with institutional strategic objectives, particularly in terms of resource optimization, governance structure, and innovation. The study addresses the gap between existing governance performance and expected capability levels within higher education institutions. Design – A descriptive qualitative design was employed. Data were collected through in-depth interviews with key stakeholders identified using RACI Chart mapping, analysis of SOP and KPI strategic documents, and direct observation of objective alignment. The evaluation focused on selected COBIT 2019 domains, namely EDM04 (resource optimization), APO01 (management framework), and APO04 (innovation). Findings – The results indicate that the EDM04 domain achieved a capability level of 3 with a score of 2.24, below the expected level 4 (2.60), resulting in a gap of 0.36. The APO01 domain also reached level 3, indicating moderate maturity in governance structure, while the APO04 domain recorded a lower score of 1.58, reflecting weak innovation governance. These findings confirm that IT governance implementation remains suboptimal and requires systematic improvement. Research implications – The study is limited to a single institutional context, which restricts generalizability. The reliance on qualitative data and the absence of integrated financial SOPs may also affect the comprehensiveness of governance evaluation and limit deeper performance validation. Originality – This research provides a quantified baseline of IT governance capability within a higher education context in North Sumatra, offering actionable insights and strategic recommendations, particularly in formalizing resource documentation and strengthening governance processes as a roadmap for similar institutions.